Biomechanical Design and Validation of a Novel Elliptical Sleeve Pedicle Screw for Enhanced Spinal Fixation Stability - Ting-Shuo Hsu; Chang-Jung Chiang; Hsuan-Wen Wang; Yu-San Chen; Chun-Li Lin (Bioengineering)
This study aimed to develop a novel modular pedicle screw system incorporating an elliptical sleeve to conform the pedicle’s elliptical cross-section and enhance fixation strength with mechanical stability. The biomechanical evaluation was conducted based on fundamental mechanics principles, followed by a finite element (FE) analysis to assess stress distribution under compressive and torsional loads. Subsequently, mechanical testing was performed to evaluate static and fatigue bending performance and in vitro biomechanical fatigue in porcine vertebrae by pull-out testing after 5000 and 100,000 cycles to assess fixation stability. The FE analysis demonstrated that the elliptical sleeve design improved bending resistance by 1.21× and torsional resistance by 1.91× compared to conventional cylindrical screws. Mechanical testing revealed greater bending/torsion stiffness and fatigue resistance, with the elliptical sleeve screw withstanding 5 million cycles at 235.4 N, compared to 175.46 N for cylindrical screws. Biomechanical pull-out testing further confirmed significantly higher retention strength after 100,000 cycles (1229.75 N vs. 867.83 N, p = 0.0101), whereas cylindrical screws failed prematurely at 10,663 cycles due to excessive displacement (>2 mm). The elliptical sleeve pedicle screw system demonstrated enhanced fixation strength, reduced micromotion, and superior fatigue resistance, making it a promising alternative to conventional pedicle screws for improving long-term spinal fixation stability.